Modern biology - Feldkamp, Susan; Alcamo, I. Edward; Allen, Katy Z.; Armstrong, David Michael 1944- (Holt, Rinehart and Winston, 2002)
This biology textbook designed for students in grades 9 through 12 includes 10 units of study, each unit containing 3-8 chapters, research notes, literature and life connections, great discoveries notes, quick labs, and chapter investigations. The book also includes a glossary and index, as well as appendices on safety in the lab, measurement, using a microscope, interactive investigations, and an overview of classification of organisms. Some of the chapter investigations and the interactive investigations require a CD-ROM available from the publisher.